Pengaruh Biaya Lingkungan Dan Kinerja Lingkungan Terhadap Kinerja Keuangan - Adyandra Sabrina Nareswari (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to examine the impact of environmental costs and environmental performance on financial performance. The population in this study are non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023. A purposive sampling method was used to select samples and resulted in a total sample of 98 companies based on predetermined criteria. Environmental costs, which arise from natural resource management policies, emission control, and waste management, can influence company profitability. On the other hand, environmental performance that reflects the extent to which the company implements the principles of social and environmental responsibility (CSR) can affect the company's financial results. This study uses a quantitative approach with regression analysis method to test the relationship between these variables.